Evaluation of an alpha-cypermethrin + PBO mixture long-lasting insecticidal net VEERALIN® LN against pyrethroid resistant Anopheles gambiae s.s.: an experimental hut trial in M’bé, central Côte d’Ivoire - Welbeck A. Oumbouke (Parasites & Vectors, 2019)
Abstract Background Long-lasting insecticidal nets (LLINs) are the primary method of malaria prevention. However, the widespread resistance to pyrethroids among major malaria vector species represents a significant threat to the continued efficacy of pyrethroid LLIN. Piperonyl butoxide (PBO) is a synergist that inhibits the activity of metabolic enzymes of the cytochrome P450 family known to detoxify insecticides including pyrethroids. Synergist LLIN incorporating PBO and a pyrethroid may provide improved control compared to pyrethroid-only LLIN. Methods The efficacy of VEERALIN® LN (VKA polymers Pvt Ltd, India), an alpha-cypermethrin PBO synergist net was evaluated in experimental huts in M’bé, central Côte d’Ivoire against wild pyrethroid resistant Anopheles gambiae s.s. Comparison was made with a standard alpha-cypermethrin-treated net (MAGNet® LN, VKA polymers Pvt Ltd, India). Nets were tested unwashed and after 20 standardized washes. Results VEERALIN® LN demonstrated improved efficacy compared to MAGNet® LN against wild free-flying pyrethroid-resistant An. gambiae s.s. Before washing, VEERALIN® LN produced mortality of An. gambiae s.s. (51%) significantly higher than the standard pyrethroid-only net (29%) (P < 0.0001). Although there was a significant reduction in mortality with both LLINs after 20 washes, VEERALIN® LN remained superior in efficacy to MAGNet® LN (38 vs 17%) (P < 0.0001). Blood-feeding was significantly inhibited with both types of insecticide-treated nets relative to the untreated control net (P < 0.0001). Unwashed VEERALIN® LN induced significantly higher blood-feeding inhibition of An. gambiae s.s. (62.6%) compared to MAGNet® LN (35.4%) (P < 0.001). The difference persisted after washing, as there was no indication that either LLIN lost protection against biting or blood-feeding. The level of personal protection derived from the use of VEERALIN® LN was high (87%) compared to MAGNet® LN (66–69%) whether unwashed or washed. The AI content of VEERALIN® LN after 20 washes decreased from 6.75 to 6.03 g/kg for alpha-cypermethrin and from 2.95 to 2.64 g/kg for PBO, corresponding to an overall retention of 89% for each compound. Conclusions The addition of the synergist PBO to pyrethroid net greatly improved protection and control of pyrethroid-resistant An. gambiae s.s. The pyrethroid-PBO VEERALIN® LN has the potential to reduce transmission in areas compromised by pyrethroid resistance.